2020
DOI: 10.3390/biom10081133
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic Acid as an Early Indicator of Inflammation during Non-Alcoholic Fatty Liver Disease Development

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a chronic liver disease characterized by excessive lipid deposition. Lipid metabolism disturbances are possibly associated with hepatocyte inflammation development and oxidative balance impairment. The aim of our experiment was to examine the first moment when changes in plasma and liver arachidonic acid (AA) levels as a pro-inflammatory precursor may occur during high-fat diet (HFD)-induced NAFLD development. Wistar rats were fed a diet rich in fat for five weeks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 42 publications
4
41
0
Order By: Relevance
“…Additionally, recent studies have indicated that a variety of biologically active metabolites produced by ARA also have a close relationship with oxidative stress, lipid metabolism, and immune function ( Hadley et al., 2016 ; Sonnweber et al., 2018 ). It has been demonstrated that ARA metabolism plays an important role in the occurring and development of NAFLD ( Arendt et al., 2015 ; Sztolsztener et al., 2020 ). For the similar pathogenesis of NAFLD and FLHS, it is interesting to explore the relationship of ARA metabolism and FLHS.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recent studies have indicated that a variety of biologically active metabolites produced by ARA also have a close relationship with oxidative stress, lipid metabolism, and immune function ( Hadley et al., 2016 ; Sonnweber et al., 2018 ). It has been demonstrated that ARA metabolism plays an important role in the occurring and development of NAFLD ( Arendt et al., 2015 ; Sztolsztener et al., 2020 ). For the similar pathogenesis of NAFLD and FLHS, it is interesting to explore the relationship of ARA metabolism and FLHS.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolites of arachidonic acid, as lipid mediators, play an important role in regulating the physiological function and pathology of the liver, such as prostaglandin E2, prostacyclin, thromboxane A2 and leukotriene C4. When liver injury occurs, macrophages gather in the liver and activate, resulting in the release of a large number of arachidonic acid metabolites, such as toxic prostaglandins, leukotrienes, TXs, free radicals and tumor necrosis factor-α, these toxic substances directly lead to the damage of hepatocytes (Chen et al, 2011;Sun et al, 2018a;Sztolsztener et al, 2020). Arachidonic acid, as an important inflammatory lipid mediator, regulates oxidative stress in hepatocyte mitochondria through three metabolic pathways of cyclooxygenase, lipoxygenase and cytochrome P450, resulting in the oxidation of a large number of fatty acids and the formation of lipid peroxides, the deposition of collagen in the liver, aggravating the injury of hepatocytes and the activation of hepatic stellate cells, and finally accelerating the injury of hepatocytes (Sacerdoti et al, 2003;Tallima, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…After four weeks of MET and MET+SM treatment, AA profiles were reduced in the hepatic DAG lipid class. Changes in AA content are understood to be an early indicator of inflammation and NAFLD progression [54], and cytochrome P450 enzymes are supposed to be AA modulators [55]. CYP-AA metabolites HETEs and EETs have different properties and can be stored in tissue lipids.…”
Section: Discussionmentioning
confidence: 99%